Anesthesia in Emergency PDA Stenting with Pulmonary Arteri Atresia - Arif Setyo Wibowo (Syntax Corporation Indonesia, 2024)
Pulmonary atresia with an intact ventricular septum is a condition that is characterized by a complete obstruction to right ventricular outflow. This condition is fatal if untreated. Ductus arteriosus communicate between pulmonary artery and proximal descending aorta. It is essential in fetal life as a communicating shunt to send blood from right ventricle bypassing the underdeveloped lungs. Ductal patency may be lifesaving in few cyanotic congenital heart diseases to maintain pulmonary blood flow.Case Illustration : We present a case of a 1‑day‑old, 3405 g child who presented to casualty with bluish discoloration. The child had central cyanosis, tachypnea with saturation 80% on 1 L/minute nasal cannula and desaturate to 40%. Transthoracic echocardiography (TTE) revealed intact intraventricular septum with pulmonary atresia and patent ductus arteriosus (PDA). The patient scheduled to an emergency PDA stenting. A heating blanket is installed on the operation table, oxygen saturation with Pulse‑oxymeter, noninvasive blood pressure, end-tidal CO2 monitor, and temperature monitoring were done. Anesthesia induction was performed with 50% oxygen in air, fentanyl 3 µg/kg, ketamine 2 mg/kg, atracurium 0.5 mg/kg and maintained with sevoflurane. The procedure was performed about 20 to 30 minutes. After procedure, oxygen saturation was increased up to 60%. The child was successfully extubated after 24 hours in the Neonatal Intensive Care Unit (NICU) with saturation 92%.Conclusion: PDA stenting is a less invasive palliative procedure for ductal dependent complex congenital heart diseases. Anesthesiologist's role were maintaining arterial saturation and hemodynamics, securing vascular assess, maintaining temperature. It needs thorough understanding of underlying physiology.